ETHICAL CLIMATE AS GOVERNANCE: EVIDENCE FROM ISLAMIC PHILANTHROPY IN INDONESIA - Moh Rifqi Khairul Umam; Indah Piliyanti; Arian Agung Prasetiyawan (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2026)
Lack of empirical understanding about the concept of ethical climate in faith-based non-profit organizations constraints the development of a better understanding of the governance system in Islamic philanthropic organizations. To address this issue, the present study aims at examining the ethical climate in Indonesian Zakat Management Organizations (henceforth LAZs) and identifying ways to overcome ethical challenges related to the process of managing zakat and other religious funds in these institutions. In particular, a quantitative survey research method was used where data from 117 respondents employed in administrative positions in national-, provincial-, and regency-level LAZs in Surakarta municipality were collected through a non-probability criterion-based sampling technique. For data collection, the modified Ethical Climate Questionnaire was utilized. In terms of data analysis, the authors employed IBM SPSS Amos software to perform the confirmatory factor analysis. The results of data analysis presented five types of ethical climate, including caring, law and code, rules, instrumental, and independence, that show the coexistence of collective orientation and individual interests among managers of LAZs. Thus, it can be stated that orientations towards both welfare and regulation as well as self-interest coexist within LAZs. The validated model developed by this study serves as a basis for further analyses concerning the effect of ethical climate on managerial decisions and organizational behaviour.